Centro de Oncologia Bucal (COB) - Cocato, Anne Cristina de Faria; Santos, Daniela Micheline dos; Ribeiro, Daniene Tesoni Cassavara; Biasoli, Éder Ricardo; Miyahara, Glauco Issamu; Silva, Janaína Zavitoski da; Silva, Jane Fátima Mendes Fernandes da; Teixeira, Jefferson Gardenal; Garcia, José Fernando; Dias, Lúcia Cavassana; et al. (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação Anne Cristina de Faria Cocato Glauco Issamu Miyahara Janaína Zavitoski da Silva